PROPERTIES AND MORPHOLOGICAL OF MORTAR CONTAINING USED ENGINE OIL - Andrie Harmaji; Andikah Willy Ramadhan (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2022)
Engine oil has an important role in the design and operation of all automotive engines. Used engine oil is a waste product produced in high quantity in the workshop garage which commonly found in most cities in Indonesia. The utilization of used engine oil has shown potential as retarder by reduce the setting time of mortar. In this study mortar was made by mixing cement,light aggregate, water, and engine oil both new and used as admixture ranged 0-1%. Mortar sample treatment is carried out at room temperature. The samples were tested for setting time and compressive strength after 3, 7 and 28 days curing. Scanning Electron Microscope characterization was carried out to to find out the morphological structure of resulting mortar. Results shown that the mortar with the addition of 0.75% used engine oil has the highest compressive test result of 9.31 MPa when the mortar reached 28 days compared to mortar without engine oil addition has a compressive test result of 7.546 MPa. SEM Images shown there are more ettringite presents in mortar with used engine oil addition.